2013
DOI: 10.1088/1748-9326/8/2/025003
|View full text |Cite
|
Sign up to set email alerts
|

Situated lifestyles: I. How lifestyles change along with the level of urbanization and what the greenhouse gas implications are—a study of Finland

Abstract: An extensive body of literature demonstrates how higher density leads to more efficient energy use and lower greenhouse gas (GHG) emissions from transport and housing. However, our current understanding seems to be limited on the relationships between the urban form and the GHG emissions, namely how the urban form affects the lifestyles and thus the GHGs on a much wider scale than traditionally assumed. The urban form affects housing types, commuting distances, availability of different goods and services, soc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
91
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 153 publications
(102 citation statements)
references
References 49 publications
3
91
0
2
Order By: Relevance
“…The decomposition of "origin" and "destination" of embodied emissions by sector in the carbon map is just an additional step introduced by but consumption-based emissions (or CFs) of cities have been calculated with (multi-region) input-output analysis before [42][43][44][45][46]. The MRIO table for this study was derived from the Australian Industrial Ecology Virtual Laboratory [47] (see the heat map in the Figure S1), which can distinguish regions with a population of 10,000 residents (denoted SA2 region) [48].…”
Section: Methodology and Datamentioning
confidence: 99%
“…The decomposition of "origin" and "destination" of embodied emissions by sector in the carbon map is just an additional step introduced by but consumption-based emissions (or CFs) of cities have been calculated with (multi-region) input-output analysis before [42][43][44][45][46]. The MRIO table for this study was derived from the Australian Industrial Ecology Virtual Laboratory [47] (see the heat map in the Figure S1), which can distinguish regions with a population of 10,000 residents (denoted SA2 region) [48].…”
Section: Methodology and Datamentioning
confidence: 99%
“…Food, transport-related services, and recreation are the top single contributors to indirect energy use and carbon emissions in various countries [23,64,66]. Several studies have shown that despite the benefits of urban density, metropolitan and inner-city living is linked to intensive consumption patterns in relation to non-energy products, which increase the indirect carbon emissions of households, thus diminishing the resource-use 'win' from lower levels of driving [15,16,[67][68][69][70]. Other studies have shown either opposite results due to the different distribution of affluence [71,72] or marginal impact of urbanity [66].…”
Section: Introductionmentioning
confidence: 99%
“…Concerning the signifi cant negative correlation between census tract population density and both vehicle and total GHGEs (i.e. the more dense a census tract, the less car usage), there is evidence in the literature for this relationship: those in more urban areas "share" more resources, have greater access to public transportation, and drive less (Dargay, 2002;Heinonen et al, 2013;Jones and Kammen, 2014). 39 Th ere is also a signifi cant negative correlation between census tract percentage of bachelor degrees (or above) and vehicle footprint; apparently census tracts with higher levels of education are producing relatively lower driving impacts.…”
mentioning
confidence: 99%